USA swimming age classification: are current competitive age-groups appropriate? - Kojima, K. (2010)
Matching youth sports participants in order to make competition fair and safe is an important goal of sports federations. USA Swimming has established 4 unisex age-groups based on chronological age (CA): 10 years & under, 11-12 years, 13-14 years, and 15 years & over. Due to considerable differences in growth and maturational status among adolescents within any given CA (Baxter-Jones, 1995; Malina & Beunen, 1996), combining swimmers of different ages into groups may not ensure fair competition. Because younger aged or late-maturing swimmers within an age-group are physically behind their same age-group older or precocious peers, the current age-grouping system may discourage them to continue competitive swimming. In addition, there is no historical rationale for the current USA Swimming age classification. The purposes of the study were to evaluate the current age classification enforced by USA Swimming and to provide an analytical rationale in support of the current or alternative age-groupings. Swim times of the top 100 U.S. women and men swimmers for each age (5 to 20 years) and a group of 21 years and over (a total of 17 separate age-groups for each sex) were acquired through the website of USA Swimming for 2005, 2006, and 2007. Data for each age were pooled over the past three years (2005-2007) and averaged for seven swim events (50-, 100-, and 200-yard freestyle, 100-yard backstroke, breaststroke, and butterfly, and 200-yard individual medley). A 17 × 2 × 7 (age × sex × event) ANOVA with Tukey`s post-hoc test was used to analyze the differences in swim time among ages and to propose alternative age-groups. The study found significant age-related differences in swim performance between each CA up to 15 years old in women and 17 years old in men for most events. Because there were differences in swim performance within the current defined age-groups, stratifying swimmers based on a single age may be a better way for ensuring fairness and equality in competition. The age-related differences in swim time occur later in men when compared with women. This may be due to sex-difference in timing of growth and maturity. The differences between sexes become greater with age but no significant sex-difference was found in 7 years and under age categories. Thus, based upon swim performance, there is no rationale for swimmers under the age of eight to compete in separate unisex categories.